Optimum temperature and chlorine ion concentration for hydrogen peroxide treatment of titanium dental implant material - Mohammad Khodaei; Farahnaz Nejatidanesh; Mohammad Javad Shirani; Srinivasan Iyengar; Hossein Sina; Alireza Valanezhad; Omid Savabi (Journal of Materials Research and Technology, 2020)
Hydrogen peroxide treatment is a cost-effective and simple method to improve the bioactivity of titanium implants. In this study, the effects of chloride ion concentration and temperature of hydrogen peroxide on the surface treatment of titanium were investigated using X-ray diffractometry (XRD), Field Emission-Scanning Electron Microscopy (FESEM), and tests in order to determine wettability and apatite forming ability. The results showed that at the lower temperatures of treatment (60 °C), hydrogen peroxide corroded the formed titania layer and the post-heat treatment resulted in rutile formation on the surface of titanium. At higher temperatures of treatment (100 °C), a uniform and crack-free anatase layer was formed on the surface of titanium, leading to the improvement of superhydrophilicity and the apatite forming ability of titanium. However, these properties were affected by increasing the chloride concentration of hydrogen peroxide. At appropriate conditions, titanium dental implant surfaces could be treated effectively using hydrogen peroxide, such that the time of treatment could be reduced to 5 h.